Anticancer activity of diosgenin and its semi-synthetic derivatives: Role in autophagy mediated cell death and induction of apoptosis - Bhardwaj N.; Tripathi N.; Goel B.; Jain S.K. (My University, 2025)
During cancer progression, the unrestricted proliferation of cells is supported by the impaired cell death response provoked by certain oncogenes. Both autophagy and apoptosis are the signaling pathways of cell death, which are targeted for cancer treatment. Defects in apoptosis result in reduced cell death and ultimately tumor progression. The tumor cells lacking apoptosis phenomena are killed by ROS-mediated autophagy. The autophagic programmed cell death requires apoptosis protein for inhibiting tumor growth; thus, the interconnection between these two pathways determines the fate of a cell. The cross-regulation of autophagy and apoptosis is an important aspect to modulate autophagy, apoptosis and to sensibilise apoptosis-resistant tumor cells under metabolic stress and might be a rational approach for drug designing strategy for the treatment of cancer. Numerous proteins involved in autophagy have been investigated as the druggable target for anticancer therapy. Several compounds of natural origin have been reported, to control autophagy activity through the PI3K/Akt/mTOR key pathway. Diosgenin, a steroidal sapogenin has emerged as a potential candidate for cancer treatment. It induces ROS-mediated autophagy, inhibits PI3K/Akt/mTOR pathway, and produces cytotoxicity selectively in cancer cells. This review aims to focus on optimal strategies using diosgenin to induce apoptosis by modulating the pathways involved in autophagy regulation and its potential implication in the treatment of various cancer. The discussion has been extended to the medicinal chemistry of semi-synthetic derivatives of diosgenin exhibiting anticancer activity. © 2021 Bentham Science Publishers.